A guanidine phosphate-assisted boron nitride network enabled simultaneous improvements in flame resistance and thermal conductivity of polyvinyl alcohol (PVA). (December 2022) - Xu, Wenzong; Xu, Chengwen; Liu, Julan; Ding, Ding; Zhang, Yi; Zhou, Yaocheng
Highlights: Polyvinyl alcohol composites were prepared by solution blending. The flame retardant and thermal conductivity of PVA were improved. 2 wt.%SiO2 @BN and 8 wt.%GP PVA had the best flame-retardant effect. Abstract: Polyvinyl alcohol (PVA) plays an important role in many fields, but its flammability in air limits its wider application. In this work, SiO2 @BN, a flame-retardant and heat conductive filler, were synthesized by hydrolysis of ethyl orthosilicate, and its structure and morphology were characterized successfully. SiO2 @BN and guanidine phosphate (GP) were mixed evenly in the solution and added to PVA to form PVA composites. Based on the data of thermal conductivity, limiting oxygen index (LOI) and cone calorimeter test (CCT), the thermal conductivity and flame retardancy of the composite were studied, and the flame retardancy mechanism was explained. The results showed that the thermal conductivity of the PVA composite added with 2 wt.% SiO2 @BN and 8 wt.% GP was 82.4% higher than that of pure PVA, and its LOI value reached 28.4%, which was 38.5% higher than that of pure PVA. The peak heat release rate (pHRR) and total heat release (THR) of the composites was 65.2% and 44.4% lower than those of pure PVA, respectively. The main reasons were the physical barrier effect of BN and SiO2, the dilution of the noncombustible gas generated by the decomposition of GP when heated, and the dehydration and carbonization of PVA promoted by the generated phosphoric acid, metaphosphoric acid and other substances.